Pengaruh Model Pembelajaran Snowball Throwing Terhadap Minat Kelas III SDN Prapag Kidul 03 - Nurpratiwiningsih, Laelia; Inayah, Tanjali; Setiyoko, Didik Tri (Peneliti.net, 2024)
This study aims to determine the effect of the snowball throwing learning model on the interest of class III SDN Prapag Kidul 03 in Maths material theme 7 subtheme 2